2020
DOI: 10.1111/rda.13604
|View full text |Cite
|
Sign up to set email alerts
|

Examination of jackass (Equus asinus) accessory sex glands by B‐mode ultrasound and of testicular artery blood flow by colour pulsed‐wave Doppler ultrasound: Correlations with semen production

Abstract: The accessory sex glands play a major role in the production of seminal plasma, and testicular artery blood flow seems to strongly influence testicular function. However, very little ultrasound imaging of these organs has been undertaken in donkeys. The present work reports the results of such examinations in five jackasses along the year. The accessory glands were inspected by B‐mode ultrasound while the testicular artery blood flow was assessed by colour pulsed‐wave Doppler ultrasound. The testicular artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 23 publications
1
25
2
Order By: Relevance
“…Ultrasonography is an easily applicable non‐invasive method for assessing the gonad and accessory sex gland and detecting different pathologies, and provides information related to the clinical fertility evaluation of animals (Kandiel & Shafey, 2017). Although ultrasound examination of gonads and accessory gonads in donkeys has been reported (Contri et al., 2008; Gacem et al., 2020; Pricking et al., 2017), studies on the effects of seasons on the glands are limited. Abou‐Elhamd et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultrasonography is an easily applicable non‐invasive method for assessing the gonad and accessory sex gland and detecting different pathologies, and provides information related to the clinical fertility evaluation of animals (Kandiel & Shafey, 2017). Although ultrasound examination of gonads and accessory gonads in donkeys has been reported (Contri et al., 2008; Gacem et al., 2020; Pricking et al., 2017), studies on the effects of seasons on the glands are limited. Abou‐Elhamd et al.…”
Section: Discussionmentioning
confidence: 99%
“…Gacem et al. (2020) reported bulbourethral glands and ampulla sizes were inversely correlated with sperm motility of jackass. In contrast, Contri et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, comparative studies in both species have identified differences in reproductive strategy as well as in the sperm form and function [15,16]. Effectively, the donkey testis is bigger and has been proved to have more efficient spermatogenesis than a stallion [17][18][19][20]. In effect, donkey sperm heads are smaller with a larger mid-piece than the stallion resulting in differences in motility patterns [21].…”
Section: Introductionmentioning
confidence: 99%